Driving Competitive Advantage in Cleantech Companies: A Model of Smart Regulation, Organizational Agility, and Technological Innovation - Matheus Eurico Soares de Noronha; Juliano Barros Neves Martins; Tamires Lietti; Rosemeire de Souza Vieira Silva (Centro Universitário Adventista de São Paulo, 2022)
Objective: The paper aims to present a propositional model that encompasses the theoretical lenses of Organizational Agility (OA) by boosting Diffusion of Technological Innovation (DTI) in companies and clean technology to obtain Competitive Advantage (CV).  Methodology: A multiple case study with a qualitative approach was carried out with Cleantech organizations, supported by 22 semi-structured interviews from 17 clean technology companies in the areas of ​​renewable energy, energy efficiency and commercialization in addition to water treatment. The results were supported by the content analysis technique.  Results: The AO can potentialize the DTI to achieve competitive advantage. Behind this, new categories were founded in this research: Agile Culture Values as a background for Digital Transformation to create a Smart Regulation to promote technological innovation in products and services at companies with sustainable solutions.  Contribution: This article contributes with a new model matching by the perspective of OA modify the positioning of managers and founders, to amplify the diffuser scenario of innovation and technology in the organization, reverberating in new market positions. The scientific contribution lists a research program based on the emerging categories of work, flowing into advances in the research field of Cleantech Organizations.